Description of the immature stages, biology and DNA-barcoding of Quichuana pogonosa (Diptera: Syrphidae) collected in Bromeliaceae in Paraná, Brazil - Echeverry,Angela (2021)
ABSTRACT Quichuana Knab, 1913 is a Neotropical genus of flower flies (Diptera: Syrphidae) with 50 valid species. Adults of this genus are flower visitors and their larvae are usually associated with the phytotelmata of bromeliads and heliconias, actively participating in the recycling of nutrients in forest environments. Despite their importance in ecosystem dynamics, Quichuana larvae are poorly known. Herein we describe the immature stages of Quichuana pogonosa Fluke, 1937 from samples collected from the phytotelmata of two terrestrial bromeliad species in the state of Paraná, Brazil. We provide illustrations of the egg, third instar larva and puparium, as well as information on the life cycle of the species. Additionally, we describe and illustrate the male genitalia and present the DNA-barcoding based on larva and adult specimens.